A Note on Wright-type Generalized q-hypergeometric Function - Chaudhary, K. K.; Rao, S. B. (Izvestiâ Irkutskogo gosudarstvennogo universiteta. Seriâ "Matematika" (Online), 2024)
In 2001, Virchenko et al. published a paper on a new generalization of Gauss hypergeometric function, namely Wright-type generalized hypergeometric function. Present work aims to define the q-analogue generalized hypergeometric function, which reduces to generalized hypegeometric function by letting q tends to one, and study some new properties. Convergence of the series defining generalized q-hypergeometric function and properties including certain differentiation formulae and integral representations have been deduced.